Dynamic modelling in development plannin - Grandinetti, L; Pezzella, F; La Bella, A (1977)
In this paper a dynamic regional model is proposed, aimed at understanding and forecasting the dynamic response of the population to many different investment policies in the agricultural, services and industrial sectors. In spite of its generality, the model has been conceived in order to be applied to underdeveloped regions. Particularly, from the demographic point of view, attention has been focused on migration phenomena; from the economic point of view, attention has been focused mainly on the rate of growth of the capital stock. Modularity is another feature of the proposed model; it is made of seven submodels which describe in a very aggregated form the evolution of the regional socio-economic system. The outputs of the submodels are then spatially distributed using a set of 'spatial operators' which take into account many social and economic factors relevant to the sub-areas into which the region can be divided. © 1977.